Pengaruh Elektrifikasi Terhadap Produk Domestik Regional Bruto Per Kapita: Studi Empiris Tahun 2014 – 2019 - Widyamantara, Putu Yogi; Khoirunnurofik, Khoirunnurofik (Universitas Pendidikan Ganesha, 2021)
This study aims the effect of electrification on productivity. We used data panel on kabupaten dan kota level with 2014-2019 period. The method in this research is descriptive quantitative with the data used is secondary data in the form of GDRB panel data throughout Indonesia In this study, productivity defined as GDRB per capita. Estimation result shows that the electrification ratio has a positive and significant effect to GDRP per capita on 2014-2019 nationally, in Sumatera island, and Kalimantan island. The presence of electrification can support productivity, such as lightning, use of mahines more efficiently, home appliance, and ICT or communication. Therefore, electrification should be fulfilled in Indonesia to increase GDRP per capita growth.